Validation of a home safety questionnaire used in a series of case-control studies. Issue 5 (3rd March 2014) - Watson, Michael; Benford, Penny; Coupland, Carol; Clacy, Rose; Hindmarch, Paul; Majsak-Newman, Gosia; Deave, Toity; Kendrick, Denise
Abstract : Objective: To measure the validity of safety behaviours, safety equipment use and hazards reported on a questionnaire by parents/carers with children aged under 5 years participating in a series of home safety case-control studies. Methods: The questionnaire measured safety behaviours, safety equipment use and hazards being used as exposures in five case-control studies. Responses to questions were compared with observations made during a home visit. The researchers making observations were blind to questionnaire responses. Results: In total, 162 families participated in the study. Overall agreement between reported and observed values of the safety practices ranged from 48.5% to 97.3%. Only 3 safety practices (stair gate at the top of stairs, stair gate at the bottom of stairs, stairs are carpeted) had substantial agreement based on the κ statistic (k=0.65, 0.72, 0.74, respectively). Sensitivity was high (≥70%) for 19 of the 30 safety practices, and specificity was high (≥70%) for 20 of the 30 practices. Overall for 24 safety practices, a higher proportion of respondents over-reported than under-reported safe practice (negative predictive value>positive predictive value). For six safety practices, a higher proportion of respondents under-reported than over-reported safe practice (negative predictive value<positive predictive value). Conclusions: This study found that the validity of self-reports varied with safety practice. Questions with a high specificity will be useful for practitioners for identifying households who may benefit from home safety interventions and will be useful for researchers as measures of exposures or outcomes.